Effect of nutrient management on leaf physiology and grain filling at late growth stage in hybrid rice - LI Zhi-gang; YE Zheng-qian; YANG Xiao-e; V. V. Virmani (浙江大学学报. 农业与生命科学版, 2003)
A field experiment was conducted to study the effect of nutrient management on rates of grain filling, photosynthesis and respiration of flag leaf during grain filling period, and grain yield of hybrid rice in comparison with the conventional rice cultivar. Applied with the same amount of NPK fertilizers, the timing and times of NK application greatly influenced grain yield of hybrid rice. That when NK was applied only as basal and tiller promoting fertilizer resulted in lowest single grain weight and total grain yield. At heading, the late stage of rice growth, top dressing with NK (10% of total of NK) together with a spray of (Zn+B and BR) markedly increased grain yield especially in the hybrid rice. The yield increase of hybrid was attributed to improvement of plant growth and delay of plant senescence. Top dressing with NK at heading resulted in significant increase of photosynthetic rate and grain filling rate, prolonged duration of the grain filling period, and increase of single grain weight and grain setting. These results implied that grain development and ripening of hybrid rice grains are not totally genetically controlled, but regulated by nutrient management remarkably, especially NK and micronutrient such as B and Zn supply at the late growth stage. Nutrient management at late stage of rice growth also improved quality of rice grains such as increasing content of some amino acids including Asp, Lys, Ala, Gln. Moreover, rice Zn content was increased when Zn addition to the spray.